Dissemination of the Activities of the Lithuanian Language Society and Other Similar Non-governmental Organizations in the Periodical “Gimtoji Kalba” - Urnėžiūtė, Rita (Lietuvių kalba, 2024)
After the restoration of Lithuania’s independence in 1990, non-governmental organizations devoted to the linguistic education, the teaching of the Lithuanian language and its popularisation, and the rights of the state language, that had been active during the interwar period, began to be re-established. The most prominent of the organizations restored were the Lithuanian Language Society and the Union of Teachers of Lithuanian Language and Literature. During the years of the restored independence, various new organizations emerged whose aims and activities had more or less in common with those of the Lithuanian Language Society and the Union of Teachers of the Lithuanian Language and Literature. In 1990, the language popularisation periodical “Gimtoji kalba” [Mother Tongue], which had been established in Kaunas in 1933, was restored. The object of the analysis is the information about the activities of non-governmental language organizations published in the restored periodical. The main focus is on the Lithuanian Language Society, a non-governmental organization that was the editor (1935–1937 in Lithuania, 1958–1968 in the USA) and the publisher (1938–1941 and 1990–1996 in Lithuania) of the “Gimtoji kalba”. The aim of the paper is to highlight and summarise the changes in the goals of the Lithuanian Language Society, the development of its activities, and the search for new forms of activities, as reflected in the publications of “Gimtoji kalba”. Descriptive, analytical and summarizing methods were applied. The analysis of the publications in “Gimtoji kalba” shows that the restored Lithuanian Language Society, which at first based its activity on the experience of the interwar period and the language movement of 1968–1988, contributed to the development of the state language surveillance system. The development of the state language surveillance system has led to a change in the direction of the Society’s activities. While at the beginning of the restoration of independence the focus was on language correctness and its maintenance, over time the Lithuanian Language Society became increasingly oriented towards linguistic education of society and promotion of the Lithuanian language.